Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1364/ao.389617
|View full text |Cite
|
Sign up to set email alerts
|

Generation and measurement of high-order optical vortices by using the cross phase

Abstract: the generation and measurement of optical vortex (OV) are the basis for a variety of related applications. However, the special case of high-order OVs has not been sufficient addressed yet. Herein, a generation and measurement method of high-order OV via utilizing the CP is investigated. In the experiment, we generate OVs with 60 l  , 20 p  and successfully measure OVs with 200 l  , 0 p  , where experimental results agree well with simulation outcome. On this basis, the intensity distributions of LG and HG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…It was theoretically found that the inter-conversion between HG and LG modes can be done with a cross phase [32]. Then Wang et al experimentally realized the inter-conversion between two modes [33]. The method with the CP amd the method of π/2 converter are both based on the astigmatism principle, where the former uses holograms instead of cylindrical lenses, which is more conducive to the precise manipulation of the optical field and greatly evades the harsh requirements of the relative position for cylindrical lenses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was theoretically found that the inter-conversion between HG and LG modes can be done with a cross phase [32]. Then Wang et al experimentally realized the inter-conversion between two modes [33]. The method with the CP amd the method of π/2 converter are both based on the astigmatism principle, where the former uses holograms instead of cylindrical lenses, which is more conducive to the precise manipulation of the optical field and greatly evades the harsh requirements of the relative position for cylindrical lenses.…”
Section: Introductionmentioning
confidence: 99%
“…The method with the CP amd the method of π/2 converter are both based on the astigmatism principle, where the former uses holograms instead of cylindrical lenses, which is more conducive to the precise manipulation of the optical field and greatly evades the harsh requirements of the relative position for cylindrical lenses. However, in [32] and [33], LG and HG beams' conversion accomplished in the far plane (Fraunhofer region), and the width of converted beam cannot be adjusted, so the conversion only with a cross phase is not available in practical application if the width of converted beam is required. Actually, with a lens, optical beam's Fraunhofer diffraction can be realized in the focal plane of the lens, and the width of the beam in the focal plane can be adjusted with the focal length of lens.…”
Section: Introductionmentioning
confidence: 99%
“…By additionally introducing a quarter wavelength waveguide section, a quasi-Laguerre-Gaussian mode with non-zero angular momentum is generated from an input E 21 mode with zero angular momentum. Conversion between Hermite-Gaussian and Laguerre-Gaussian beams in free-space has been demonstrated with cylindrical lenses [11]- [13], holograms that introduce a cross-phase [14], [15], and metasurfaces that induce a Pancharatnam-Berry phase [16]- [18]. Metasurfaces vary polarization adiabatically over a closed circuit to introduce a geometric phase.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, the CP, a new kind of phase structure, has been involved in Laguerre-Gauss (LG) beams that open up a new horizon for generation and measurement of optical vortices [6,14]. Recently, we investigated a generation and measurement method of high-order optical vortices via the CP, which has been experimentally achieved [15]. In August 2020, we proposed a new type of CP, which can be employed to modulate optical vortices to implement shaping and multi-singularity manipulation simultaneously in the far-field [16].…”
mentioning
confidence: 99%